The impolitic in question. An analysis of the crisis of modern juridical-political notions in the objections to Roberto Esposito’s categorie dell’impolitico - Bialakowsky, Guillermo (2024)
This article aims to examine the objections to impolitical perspective arising from the publication of Roberto Esposito's book Categorie dell’impolitico (1988). The hypothesis of this paper is that the various positions on the impolitical have as a condition of possibility two different perspectives on the crisis of modern juridico-political notions. In order to elucidate the distinction between “overcoming” and “ulteriority”, it is crucial to analyze the reading proposed by the Italian author himself in the Preface to the second edition of Categorie dell’impolitico (1999). The systematic approach to this question will lead, towards the end of the article, to raise the question about the productivity and relevance of the impolitical point of view in the contemporary debate.